2013
DOI: 10.1055/s-0032-1331711
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Characterization and Antimicrobial Activity of Substituted Thiazolyl Derivatives of 2-Quinolones

Abstract: A series of new 3-(2-substituted amino/substituted hydrazino-1,3-thiazol-4-yl)-4-hydroxy-1-methyl/phenylquinolin-2 (1H)-one hydroiodide 3a-3f and 4a-4f derivatives were prepared by heating 3-Acetyl-4-hydroxy-1-methyl/phenyl quinolin-2 (1H)-one 2a-2b with substituted thiourea and substituted thiosemicarbazide in presence of iodine in n-butanol. The title compounds were characterized on the basis of IR, 1H NMR, 13C NMR and Mass spectral (MS) studies. Further title compounds were evaluated for antibacterial and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Many strains of tuberculosis resist to the drugs mostly used to treat the disease and as a result new drugs and regimens are urgently needed to shorten the required duration of tuberculosis treatment [2][3][4][5][6]. N-Adamantan-2-yl-N'-[(E)-3,7-dimethylocta-2, 6dienyl]ethane-1,2-diamine (SQ109, ▶ Fig. 1), is a drug candidate that is active against both drug-susceptible and drug-resistant TB strains and affects cell wall synthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many strains of tuberculosis resist to the drugs mostly used to treat the disease and as a result new drugs and regimens are urgently needed to shorten the required duration of tuberculosis treatment [2][3][4][5][6]. N-Adamantan-2-yl-N'-[(E)-3,7-dimethylocta-2, 6dienyl]ethane-1,2-diamine (SQ109, ▶ Fig. 1), is a drug candidate that is active against both drug-susceptible and drug-resistant TB strains and affects cell wall synthesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…2‐Quinolone‐thiazole hybrids 2 and 3 (Figure ) demonstrated potential antifungal activities against A. niger and C. albicans with MIC of 25–100 μg/ml, but they were less potent than the reference fluconazole (MIC: 12.5 μg/ml) . The SAR revealed that the introduction of substituted phenyl groups at thiazole fragment (R 2 ) could not improve the activity, and hybrids with –MePh at thiazole motif were less active than the analogs with –ClPh.…”
Section: ‐Quinolone Derivativesmentioning
confidence: 99%
“…[35,36] 2-Quinolone-thiazole hybrids 2 and 3 ( Figure 3) demonstrated potential antifungal activities against A. niger and C. albicans with MIC of 25-100 μg/ml, but they were less potent than the reference fluconazole (MIC: 12.5 μg/ml). [37] The SAR revealed that the introduction of substituted phenyl groups at thiazole fragment (R 2 ) could not improve the activity, and hybrids with -MePh at thiazole motif were less active than the analogs with -ClPh. Replacement of -Me at N-1 position of 2-quinolone moiety by the phenyl group could enhance the activity to some extent, and the hydrazone compounds 3 were more active than the corresponding amine derivatives 2 generally.…”
mentioning
confidence: 99%
“…In the search for a new scaffold for antimicrobial drugs, 4-hydroxy-2-quinolone, a class of heterocyclic compound, has shown great potential, as various analogs of 4-hydroxy-2-quinolone including Roquinimex (Linomide), a synthetic immunomodulator [ 3 ], have been reported to possess a wide range of biological activities such as antibacterial [ 4 ], antifungal [ 5 ], anticancer [ 6 ], antioxidant [ 7 ], and so on. Over the past few decades, several attempts have been made to investigate the structure–activity relationship of the antimicrobial activity of this scaffold; for instance, the derivatives of 4-hydroxy-2-quinolone bearing chalcones [ 8 ], pyrimidines [ 9 ], pyrazoles [ 10 ], and thiadiazole [ 11 ] ( Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%